1998
DOI: 10.1063/1.476062
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectroscopy of SiH2 near 640 nm

Abstract: The à 1 B 1 -X 1 A 1 absorption spectrum of SiH 2 has been observed using intracavity laser absorption spectroscopy with an equivalent path length of up to 13.0 km and the à 1 B 1 (0, 0, 0)-X 1 A 1 (0, 0, 0) band near 640 nm recorded for the first time. The silylene radical was generated in a continuous discharge in a flowing mixture of silane in argon, giving a concentration of the order of 10 10 SiH 2 /cm 3 . The spectrum spans the region between 15350 and 16100 cm Ϫ1 . Rotational transitions have been assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
(53 reference statements)
2
34
1
Order By: Relevance
“…These diradicals are popular as benchmark systems, [33][34][35][36][37][38][39]41,60 because of their small size ͑but rich electronic structure͒, and the availability of experimental data. [61][62][63][64][65][66] For these systems, we compare the performance of the SF models against a variety of single-and multireference methods, and investigate the convergence of different methods with respect to the one-particle basis set. Next we consider a set of diatomic molecules with a diradical singlet state ͑NH, NF, OH ϩ , and O 2 ͒ for which accurate experimental data are available.…”
Section: B Computational Detailsmentioning
confidence: 99%
“…These diradicals are popular as benchmark systems, [33][34][35][36][37][38][39]41,60 because of their small size ͑but rich electronic structure͒, and the availability of experimental data. [61][62][63][64][65][66] For these systems, we compare the performance of the SF models against a variety of single-and multireference methods, and investigate the convergence of different methods with respect to the one-particle basis set. Next we consider a set of diatomic molecules with a diradical singlet state ͑NH, NF, OH ϩ , and O 2 ͒ for which accurate experimental data are available.…”
Section: B Computational Detailsmentioning
confidence: 99%
“…The most obvious explanation for the observed bi-exponential behavior is that two or more different transitions were simultaneously excited due to a blending of lines. 14 The LIF excitation data set for SiHD (Table I) is less extensive than the data sets associated with the previous visible 25 or infrared 26 absorption spectra of SiH 2 due mainly to the small fluorescence quantum yield for the higher rotational levels of theà 1 A ′′ state. Accordingly, the spectroscopic parameters for SiHD are somewhat less well determined than those for SiH 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Initial assignment of the c-type transitions in the excitation spectrum was readily accomplished by predicting the spectrum using estimated rotational parameters based upon the previously determined structure 25 of SiH 2 . Combination/differences revealed that the energies were not severely perturbed.…”
Section: A Energies and Transition Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The first excited triplet state (ã 3 B 1 ) of SiH 2 is around 7000 cm −1 [54] while the first excited singlet state (Ã 1 B 1 ) lies at 15 500 cm −1 [55]. The presence of these states would have had an effect on the accuracy of the computed ab initio PES and DMS, due to Renner-Teller and spin-orbit interactions between these electronic states, which were not taken into account here.…”
Section: The Cats Line Listmentioning
confidence: 99%